Anglicanorum Coetibus art. 1 §§1-2: Erection of the personal ordinariate (Roman Replies and CLSA Advisory Opinions 2011, 2011)
"The Congregation for the Doctrine of the Faith issued a Circular Letter calling for each Episcopal Conference in the world to develop guidelines for handling allegations of clerical sexual abuse of minors. The Circular letter contains themes as well as canonical legislation for consideration by episcopal conferences. The guidelines are to be developed within a year. The letter from Cardinal William Levada, Prefect of the Congregation for the Congregation of the Faith, and the Circular Letter follow."